Penetration factors and introduction possibility for image diagnostic equipment. Issue 2 (June 2018) - Suzuki, Teppei; Isomi, Yusuke; Tsuji, Shintaro; Tani, Yuji; Tanikawa, Takumi; Yamasina, Hiroko; Ogasawara, Katsuhiko
Abstract: Background: This study investigated and analyzed the relationship between medical resources and economic conditions of OECD member countries and extracted factors for introducing imaging diagnostic equipment in each country. We also investigated the possibility of introducing diagnostic imaging equipment. Methods: A principal component analysis was conducted from medical environment indices and economic situation indices; the results were visualized on a graph with the extracted two principal components as axes, and the target nations were categorized according to the possibility of introducing diagnostic imaging equipment. Next, with the number of CTs and MRIs as response variables, we visualized the probability results on a graph by conducting a multiple regression analysis with the indices as explanatory variables and extracting the most influential factors on the number of diagnostic imaging equipment introduced. Results: We classified 29 countries into four groups according to medical environment and economic situation indices. By extracting from the four groups a group with a high possibility for introducing medical equipment then conducting a multiple regression analysis with CT and MRI unit counts as objective variables and other medical environment and economic situation indices as explanatory variables, it became clear that the factor with the greatest influence on CT and MRI unit counts is the number of hospital beds. Conclusion: As topics of future studies, we would like to clarify the factors behind as well as the probability for the introduction of medical equipment in each nation by researching high-growth medical equipment markets. Highlights: We visualized factors behind the spread of diagnostic imaging equipment with a focus on OECD countries. A principal component analysis was conducted from medical environment indices and economic situation indices. We classified 29 countries into four groups by medical environment and economic situation indices. Consideration of the order of highest probability of introducing medical equipment suggests that introduction possibility is high in the United States, Mexico, Chile and Turkey.